2017
DOI: 10.1007/s11064-017-2193-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Filopodia in Cultured Astrocytes by an Algorithm

Abstract: Astrocytes in vivo extend thin processes termed peripheral astrocyte processes (PAPs), in particular around synapses where they can mediate glia-neuronal communication. The relation of PAPs to synapses is not based on coincidence, but it is not clear which stimuli and mechanisms lead to their formation and are active during process extension/ retraction in response to neuronal activity. Also, the molecular basis of the extremely fine PAP morphology (often 50 to 100 nm) is not understood. These open questions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…In this study, L-type voltage-gated calcium channels (CaV) are shown to play a significant role in the glutamate-induced filopodiagenesis of astrocyte model cells U118-MG. Of the three protein subtypes constituting L-type CaV, the α2δ subunit appears essential to control filopodia extension, while the transmembrane channel α1 subunit may only be partially involved. These results are consistent with what has been observed in primary astrocytes (Cornell-Bell, Thomas, and Caffrey 1992;Cornell-Bell, Prem, and Smith 1990;Araque et al 1999;Aumann et al 2017). In our study, sequestering the extracellular calcium during glutamate stimulation prevented the protrusion of cell processes; while, sequestering the intracellular calcium still elicited about a third of the response (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, L-type voltage-gated calcium channels (CaV) are shown to play a significant role in the glutamate-induced filopodiagenesis of astrocyte model cells U118-MG. Of the three protein subtypes constituting L-type CaV, the α2δ subunit appears essential to control filopodia extension, while the transmembrane channel α1 subunit may only be partially involved. These results are consistent with what has been observed in primary astrocytes (Cornell-Bell, Thomas, and Caffrey 1992;Cornell-Bell, Prem, and Smith 1990;Araque et al 1999;Aumann et al 2017). In our study, sequestering the extracellular calcium during glutamate stimulation prevented the protrusion of cell processes; while, sequestering the intracellular calcium still elicited about a third of the response (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Imaging began 10 minute before stimulating cells by adding a glutamate (Alfa Aesar A15031) aliquot to obtain a final dish concentration of 100 μM glutamate. More specifically, a 20x stock solution of L-glutamate was prepared in deionized millipore water and filter-sterilized through a 0.22 μm syringe filter [15, 17]. A 10.0 μL aliquot of the 20x glutamate solution was carefully delivered to the medium (2.0 mL) at the edge of the 35 mm dish.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a novel mechanism of cell to cell communication based on cellular protrusions (filopodia) has been described in glial cells [104]. Astrocytes in vivo extend thin processes around synapses that mediate the communication with neurons.…”
Section: Cytonemes In Nonepithelial Tissues: Trachea Myoblast Ovmentioning
confidence: 99%
“…Astrocytes in vivo extend thin processes around synapses that mediate the communication with neurons. These structures are known as peripheral astrocyte processes (PAPs) and are from 50 to 100 nm thick [104].…”
Section: Cytonemes In Nonepithelial Tissues: Trachea Myoblast Ovmentioning
confidence: 99%